2014
DOI: 10.1007/s12663-013-0605-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Use of Platelet Rich Plasma in Bone Healing

Abstract: Background Tooth extraction is performed for a wide variety of reasons as we know. Several techniques aiming at enhancing the regeneration process in the extraction socket have been adopted such as filling the socket with autogenous bone grafts or bone substitutes. We know platelets play a central role in hemostasis and healing processes but relative contradictory effect of platelet in bone regenerating capacity have been published in different in vitro and in vivo studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
0
10
0
4
Order By: Relevance
“…They found that PRP acted on the initial events of the healing process, thus promoting increased osteogenic stimulation in the first month. However, there was no improvement in bone healing after 4 months of follow-up [28] . In contrast, Mariano et.…”
Section: Platelet-rich Plasma (Prp) X Platelet-rich Fibrin (Prf)mentioning
confidence: 82%
See 1 more Smart Citation
“…They found that PRP acted on the initial events of the healing process, thus promoting increased osteogenic stimulation in the first month. However, there was no improvement in bone healing after 4 months of follow-up [28] . In contrast, Mariano et.…”
Section: Platelet-rich Plasma (Prp) X Platelet-rich Fibrin (Prf)mentioning
confidence: 82%
“…The filling of the alveoli following extraction with platelet concentrates has also been the subject of study by many authors. Gawai and Sobhana (2015) [28] , extracted lower third molars of 10 patients bilaterally, and the alveolus was filled with PRP on one side. Patients were followed up clinically and radiographically after 1 week, 1, 2, 3 and 4 months.…”
Section: Platelet-rich Plasma (Prp) X Platelet-rich Fibrin (Prf)mentioning
confidence: 99%
“…concluded that application PRP to extraction socket leads to significant improvement of the soft tissue healing, but there was no added benefit in late bone healing [13].…”
Section: Discussionmentioning
confidence: 99%
“…PRP is often used in clinical studies, such as application to periodontal wound healing [6], alveolar bone healing after extraction [4] [12] [13], etc. Dutta, et al reported that they used PRP in empty extraction socket of impacted mandibular third molars, and has significant improvement in soft tissue healing and bone density in extraction sockets [12].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other platelet concentrates this technique requires neither anticoagulants nor bovine thrombin making it simple in its preparation, and considered as one of biological material that can promote osteogenesis in tooth extraction sockets and its effect is remarkable at the earlier time of bone formation (9) . Up right now, a complete preservation of the alveolar contour after tooth extraction with intra-socket grafts seems to be an unpredictable treatment goal (10) .…”
Section: Dental Journal F O R G I R L S (140)mentioning
confidence: 99%